EARLY DIAGNOSTIC OF SEPSIS IN NEWBORNS WITH RESPIRATORY DISTRESS SYNDROME - Elizabeta Shuperliska; Aspazija Sofijanova; Silvana Naunova Timovska; Sonja Bojadzieva; Avdi Murtezani (SHMSHM / AAMD, 2020)
Objective: Early diagnosis of sepsis in newborns with RDS is essential for life-threatening condition, for reducing severe sepsis and septic shock in the Intensive care Unit at the University Children’s Hospital in Skopje.Methods: In this prospective study, we included 100 (M:F=59:41) newborns with Respiratory distress syndrome (RDS) suspected for sepsis admitted in the Intensive Care Unit in period of December 2019 till 31 May 2020 y. Procalcitonin levels were measured by using a immunoassay system Vidas based on the ELFA principles. Results: The newborns with RDS suspected for sepsis have been divided into two groups The first group included 50 newborns with RDS and positive blood culture and the second group included 50 newborns with RDS and negative blood culture. Тhe average gestational age of the newborn with RDS and positive blood culture was 36,01± 3,1 weeks and the newborn with RDS and negative blood culture 36,26± 3,2 weeks. Preterm newborns in both groups dominated (64,2% and 58,2%). Тhe average birth weight of the newborn with RDS and positive blood culture was 2490,5 ±791,6 grams, and the newborn with RDS and negative blood culture was 2690,2±788,5grams. There is statistically significant difference in average PCT between the two groups overtime (p<0.05). There is statistically significant difference in average PCT between the two groups overtime procedure (MV , BCPAP, OXYGEN MASK) (p<0.05).Conclusions: PCT is promising sepsis markers in newborns with RDS, capable of complementing clinical signs and routine lab parameters suggestive of severe infection at the time of ICU admission
Keywords: procalcitonin (PCT); newborns; respiratory distress syndrome (RDS)